Interventions for zoster-associated pain: A retrospective study based on the clinical database - Chen, Lu; Li, Jun; Liu, Hui; Yang, Pingliang; Zuo, Yunxia; Ye, Ling (Frontiers in Neurology, 2022)
Background Herpes zoster (HZ)-associated pain can lead to severe pain and reduced quality of life. Exploring effective treatment and the risk factors of zoster-associated pain has become important. Methods Interventions including nerve block, radiofrequency, and thermocoagulation were used for zoster-associated pain. The data of 131 patients with HZ and 230 patients with postherpetic neuralgia (PHN) were collected at baseline, 2 weeks, 3, 6, and 12 months after the intervention. Visual analog scale (VAS) and Brief Pain Inventory (BPI) scores at different time points were analyzed by two-way repeated measures ANOVA with Group as the between-subject variable (different pain durations and areas), Time as the within-subject variable (baseline, 2 weeks, 3 months, 6 months, and 12 months), and Group × Time as the two-way interaction. Besides, the effective rate, adverse effects, and medication were also recorded. The risk factors of PHN were analyzed by logistic regression. Results A total of 25 (19.08%) patients with HZ continued to have pain in the initially affected area after 3 months. The VAS scores and the BPI quality of life scores of patients with HZ-associated pain were significantly reduced from baseline to 2 weeks, 3, 6, and 12 months after the interventions. There was no significant difference in VAS and BPI scores in different pain areas and pain durations. No significant Group × Time interaction was observed. Age, diabetes mellitus, and immune-related diseases were risk factors of PHN. Conclusion Interventions could significantly improve the pain degree and life quality of patients with zoster-associated pain, and the positive effect of intervention did not change with pain duration and area. Advanced age, diabetes, and immune-related diseases are risk factors of PHN.